Religious Behavior among Female University Students with Full Face Veil in East Kalimantan - Hidayati, Diajeng Laily (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
One form of the expressions of islamic piety among female university is the use of full face veil (known as cadar) in public sphere. Among educated young Muslim women in Indonesia, particularly in university settings in East Kalimantan, the use of cadar as an expression of piety managed to gain substantial ground since 2016. The majority of people often identify the full face veil with the fundamental Islamic movement. Full-face veil users among educated young Muslims, mostly in those resided in urban settings, reject the stigma and labels of hardliners that often attached to them. Believing that such practice as covering face constitute their very understanding of Islamic tenets, this particular group of young educated Muslim women are struggling to challenge the narrative of covering face among Muslim women as indication of backwardness, radicalism and extremism. This paper, therefore, aims at discussing religious behavior among female students who use full face veil in several universities in East Kalimantan. A combination of in-depth interviews and survey technique are utilized to collect data while thematic analysis technique is applied to analyze collected data. Findings reveal that, ideologically speakings, female Muslim university students split into two factions; one that believes wearing cadar as a highly commendable action and one that believes the act to be merely a good deed. They also feel much safer once they started wearing cadar. Most of informants agree that wearing full face veil has made their private lives much safer in comparison to before they wear full face veil. Keyword: cadar, full face veil, religious behavior, female university student, East Kalimantan